ANALYSIS OF THE IMPACT OF THE DEVELOPMENT OF DIGITAL TECHNOLOGIES ON THE LABOR MARKET - R.К. Sabirova; Zh.N. Yerniyazova; G.Е. Talapbayeva; A.К. Masalimova (Academic Journal of Physical and Chemical Sciences, 2019)
The relevance of this issue is determined by the need to create social and economic opportunities in the country for highly productive work of workers in the digital economy, their continuous development and professional realization, high incomes of digital knowledge and skills holders, and a decent standard of living for their households. This will create a competitive economy in the country with attractive conditions for life, work and employment, ensure the attractiveness of the image of Kazakhstan in the global digital economy, as well as its safety in the human dimension. The scientific idea is to form a single concept of orientation of a person, society, organizations in the professional division of labor, taking into account the interests of all subjects of social and labor relations, the prospects for the transformation of the world of professions and the labor market.